Induction of Therapeutic Hypothermia During Out-of-Hospital Cardiac Arrest Using a Rapid Infusion of Cold Saline (The RINSE Trial) - Bernard, S.; Smith, K.; Finn, Judith; Hein, C.; Grantham, H.; Bray, Janet; Deasy, C.; Stephenson, M.; Williams, T.; Straney, L.; Brink, D.; Larsen, R.; et al. (Lippincott Williams & Wilkins, 2016)
© 2016 by the American College of Cardiology Foundation and the American Heart Association, Inc. BACKGROUND—: Patients successfully resuscitated by paramedics from out-of-hospital cardiac arrest (OHCA) often suffer severe neurological injury. Laboratory and observational clinical reports have suggested that induction of therapeutic hypothermia during cardiopulmonary resuscitation (CPR) may improve neurological outcomes. One technique for induction of mild therapeutic hypothermia during CPR is a rapid infusion of large-volume cold crystalloid fluid. METHODS—: In this multi-centre, randomized, controlled trial we assigned adults with OHCA undergoing CPR to either a rapid intravenous infusion of up to two-litres cold saline or standard care. The primary outcome measure was survival at hospital discharge; secondary end-points included return of a spontaneous circulation (ROSC). The trial was closed early (at 48% recruitment target) due to changes in temperature management at major receiving hospitals. RESULTS—: A total of 1198 patients were assigned to either therapeutic hypothermia during CPR (618 patients) or standard pre-hospital care (580 patients). Patients allocated to therapeutic hypothermia received a mean (SD) of 1193 (647) mL cold saline. For patients with an initial shockable cardiac rhythm, there was a decrease in the rate of ROSC in patients who received cold saline compared with standard care (41.2% compared with 50.6%, P=0.03). Overall 10.2% of patients allocated to therapeutic hypothermia during CPR were alive at hospital discharge compared with 11.4% who received standard care (P=0.71). CONCLUSIONS—: In adults with OHCA, induction of mild therapeutic hypothermia using a rapid infusion of large-volume, intravenous cold saline during CPR may decrease the rate of ROSC in patients with an initial shockable rhythm and produced no trend towards improved outcomes at hospital discharge. CLINICAL TRIAL REGISTRATION—: www.Clinicaltrials.gov. Identifier: NCT01173393.